Identifikasi Dan Potensi Manfaat Tanaman Obat Di Taman Nasional Baluran - Kemal, Muhammad; Syahri, Alvi; Safa, Davina; Fadillah, Nurul; Yasmin, Amirah; Muliyah, Evi; Ridhwan, Muhammad; Noor, Meiry Fadilah (Journal of Natural Sciences, 2024)
Medicinal plants, or biopharmaceuticals, are plant species with properties that serve as remedies for treating and preventing diseases. This study aims to identify medicinal plant species and analyze their potential in the Evergreen Forest and Seasonal Forest of Baluran National Park. The method used is field observation with an exploration approach, recording medicinal plant species at observation sites and identifying their scientific names and medicinal uses. Baluran National Park is a conservation area that sustainably manages natural resources, including the use of medicinal plants by local communities. This study recorded 55 species of medicinal plants from 26 families utilized in traditional medicine. Plant parts used include leaves, flowers, fruits, rhizomes, bark, stems, and seeds. The seasonal forest environment also influences the active compound content of medicinal plants. The findings highlight the importance of conserving medicinal plants to support traditional use and environmental sustainability.